Phases of the exocytotic fusion pore. Issue 21 (1st October 2018) - Álvarez de Toledo, Guillermo; Montes, María Ángeles; Montenegro, Pablo; Borges, Ricardo
Abstract : Membrane fusion and fission are fundamental processes in living organisms. Membrane fusion occurs through the formation of a fusion pore, which is the structure that connects two lipid membranes during their fusion. Fusion pores can form spontaneously, but cells endow themselves with a set of proteins that make the process of fusion faster and regulatable. The fusion pore starts with a narrow diameter and dilates relatively slowly; it may fluctuate in size or can even close completely, producing a transient vesicle fusion (kiss‐and‐run), or can finally expand abruptly to release all vesicle contents. A set of proteins control the formation, dilation, and eventual closure of the fusion pore and, therefore, the velocity at which the contents of secretory vesicles are released to the extracellular medium. Thus, the regulation of fusion pore expansion or closure is key to regulate the release of neurotransmitters and hormones. Here, we review the phases of the fusion pore and discuss the implications in the modes of exocytosis. Abstract :